THE EFFECT OF BREASTFEEDING ENGINEERING HEALTH EDUCATION ON THE BEHAVIOR OF POST PARTUM MOTHERS IN SISUMUT PUSKESMAS KOTAPINANG LABUSEL IN 2021 - Nila Hayati; Mestika Rija Helti (Institute of Computer Science (IOCS), 2022)
The importance of supporting successful breastfeeding is the first time during pregnancy where a prospective mother must seek information about the advantages of breastfeeding, the benefits of breastfeeding for babies and good and correct breastfeeding techniques. This is inseparable from the importance of health education, especially health education in breastfeeding techniques. This study aims to determine the Effect of Breastfeeding Technical Health Education on the Behavior of Post Partum Mothers at the Sisumut Health Center Kotapinang Labusel in 2021. This research is a quasi-experimental research with one group pre-post test design. This research has been carried out from July 2021 to August 2021. The population is 40 people. Sampling using accidental sampling with a total sample of 28 people. The results showed that the behavior of postpartum mothers before the breastfeeding technique health education was mostly in the bad category as many as 19 people (67.9%) while the behavior of postpartum mothers after the breastfeeding technique health education was mostly well behaved as many as 26 people (92.9%). Based on the results of the Wilcoxon test, it was found that the average value before treatment was 3.39 with a standard deviation of 1.618 and after being given treatment there was an average increase to 6.54 with a standard deviation of 1.202. So it can be concluded that there is an influence of Breastfeeding Technical Health Education on the Behavior of Post Partum Mothers at the Sisumut Health Center Kotapinang Labusel in 2021. Suggestions in this study Sisumut Kotapinang Labusel improve postpartum maternal health education.